Effect of Social Media Addiction on Mental Health of Emerging Adults (Indian Journal of Extension Education, 2022)
In today’s world, many of us rely on social media. Though each has its benefits spending too much time on social media can lead to many mental health issues. So the present study on the effect of social media addiction on mental health of emerging adults was conducted in Dharwad district of Karnataka state during the year 2020-21 to assess the social media addiction and its effect on mental health of emerging adults. One hundred and sixty students were selected randomly from arts and science degree colleges of Dharwad city. Data was collected from the students by using self structured questionnaire, social media addiction scale and mental health inventory which gathered information about social media usage, social media addiction and mental health level of emerging adults respectively. Results found that majority were using 1-3 GB of data per day on social media sites and were posting pictures and videos daily on these sites. Majority were using social media without the knowledge of parents by spending more time than desired by ignoring responsibilities. There was a negative relationship between social media addiction and mental health status and using excessive social media has negative effect which is influencing academic performance.